Synthesis and Characterization of Nd:Y3Ga5O12 Nanopowder for Transparent Ceramic - Zeng, Fanming; Li, Chun; Lin, Hai; Miao, Dongwei; Liu, Jinghe (Asian Journal of Chemistry, 2014)
Nd:Y3Ga5O12(Nd:YGG) nanopowder was prepared by ammonium hydrogen carbonate co-precipitation method. The X-ray diffraction suggested that the powder became pure phase without impurities after calcined at 900 °C for 4 h. Infrared spectrum indicated that after calcined at 900 °C, the acid radical and hydroxide are all decomposed. SEM showed that the powder reveal good dispersity with the average grain size about 60 nm. Fluorescence spectra showed that the strongest emission peak located at 1062 nm, which is the transmission of 4F3/2-4I11/2 by Nd3+ ion.